Adaptation to flood risk in coastal urban area under rapid urbanization and climate change in Ho Chi Minh City, Vietnam - Tran Thanh Tu; Vilas Nitivattananon; Perera, L.A.S. Ranjith; Ahmad, Mokbul Morshed; The Netherlands (Pathum Thani, Thailand : Asian Institute of Technology, 2009)
This research develops an adaptation process to cope with flood risk in coastal cities under impact of climate change and rapid urbanization. HCMC, Vietnam was chosen as a case which is affected by climate variability such as increasing rain intensity and South China Sea level rise. The research applied Rapid Vulnerability Assessment to assess direct and indirect vulnerability as well as the community-based adaptation capacity to flood. The Tool for Environmental Assessment and Management (TEAM) was also used in evaluating the adaptation strategies to cope with flood in the context of urban water resources management. Under same natural conditions, people living in community with more urbanized have to suffer more inundation and risks from polluted floodwater than those who live in less urbanized district. However, people in lower urbanized district are more vulnerable since they have low capacity to cope with flood and pollution due to flood-prone living conditions, poverty and lack of awareness on the changing variability and water pollution. Besides, the organizational adaptation capacity is influenced by economic activities, lack of strict regulations and effective organizational and administrative structures. Gender analysis in this research has found that men and women play different roles in coping with hazards, and women suffer more risks than men especially in term of health, sexual harassment, and increasing responsibility. The research recommends that adaptation process should focus on integrating vulnerability assessment findings appropriately with TEAM and gender analysis in order to develop and implement effective and efficient adaptation measures without any conflicts and bias. This adaptation process may be applied for other countries having different contexts of development under different levels of projected climate change related risks
Submitted in partial fulfillment of the requirements for the degree of Master of Science in Urban Environmental Management
Thesis (M.Sc.) - Asian Institute of Technology, 2009
Keywords: Climatic changes -- Risk assessment -- Vietnam -- Ho Chi Minh; Floodplain management -- Vietnam -- Ho Chi Minh